Hubungan Keaktifan Mengikuti Kelas Ibu Hamil dengan Kesiapan Persalinan pada Pelayanan Kebidanan Primer - Siti Fithrotul Umami (IJMT : Indonesian Journal of Midwifery Today, 2026)
Background: Maternal readiness is an important factor influencing the smoothness of childbirth and reducing the risk of complications. One strategy to improve maternal readiness is through participation in antenatal classes. However, the level of active participation among pregnant women in such activities varies and may influence childbirth preparedness. Objective: This study aimed to analyze the relationship between participation in antenatal classes and childbirth preparedness among pregnant women in primary midwifery care settings. Methods: This study employed a quantitative approach with an analytic observational design using a cross-sectional method. The study was conducted in February 2026 at TPMB Bdn. Titik Nur Aini, S.Keb, Pasuruan Regency. The population consisted of 40 pregnant women attending antenatal classes, and 37 respondents who met the inclusion criteria were selected using total sampling. Data were collected using validated and reliable structured questionnaires. Instrument validity testing showed all items were valid (r count > r table), while reliability testing obtained a Cronbach’s alpha value of 0.82. Data were analyzed descriptively and inferentially using the Chi-Square test with a significance level of 0.05. Results: Most respondents actively participated in antenatal classes (64.9%) and were categorized as prepared for childbirth (64.9%). Statistical analysis showed a significant relationship between participation in antenatal classes and childbirth preparedness (p=0.000). Conclusion: Active participation in antenatal classes is associated with better childbirth preparedness. Strengthening maternal education and family support is important to improve maternal readiness for labor.